Novel targeted therapies for the management of liver fibrosis. (2nd January 2020) - Trivella, Juan P.; Martin, Paul; Carrion, Andres F.
ABSTRACT: Introduction : Prolonged liver injury results in tissue damage and replacement by extracellular matrix and fibrosis. Cirrhosis represents a leading cause of mortality worldwide and imposes a major financial burden on health-care systems. Fortunately, fibrogenesis has proven to be reversible if halted early, encouraging the development of novel anti-fibrotic agents that may accelerate histological restoration. Preclinical data have elucidated numerous potential therapeutic targets and many anti-fibrotic agents are currently at various stages of clinical research. Areas covered : The present review summarizes recent clinical data regarding anti-fibrotic drugs including monoclonal antibodies, targeted conjugates, and small molecule agents. Expert opinion : Although undeniable progress has been made in the development of anti-fibrotic agents in recent years, most data currently available are derived from preclinical and early clinical studies. The efficacy and safety of these agents will need to be corroborated by larger clinical trials, some of which are ongoing with results expected in the upcoming years. Combination therapy with agents targeting different pathways of fibrogenesis will also be of great interest for the future and will need to be explored in clinical trials.